Keanekaragaman dan Pemanfaatan Ubi-Ubian sebagai Alternatif Tanaman Pangan di Kecamatan Bantarkawung Kabupaten Brebes - Uswatun Hasanah; Edy Purwono Hadi; Hexa Apriliana Hidayah (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2014)
A research on the diversity and use of tuber as alternative food crops in Bantarkawung, Brebes has been conducted. This research was aimed to find out the kinds of tuber used as alternative food crops.  The method used was survey with a purposive random sampling applied to eighteen villages, The data were obtained by interviewing using questionnaire for each owner. They were analyzed descriptively for tuber type.  The result of this study showed that there are nine species of tuber plant used as alternative food crops: Manihot esculenta, Ipomoea batatas., Dioscorea alata, D. hispida, D. esculenta, Canna edulis, Colocasia esculenta, Amorphophallus campanulatus, Maranta arundinacea, and 7 cultivars from 3 species of plant that were Manihot esculenta.’ Darmo’, M. esculenta ‘Mentega’,  M. Esculenta ‘Valenca’, Ipomoea batatas. ‘Selat’, I. batatas ‘Sriwil’, Colocasia esculenta ‘Udang’ and C. esculenta ‘Pari’.  M. esculenta were more often found while D.  hispida was the less frequently used.   People in Bantarkawung used tuber as the alternative food crops for self consumption by boiling, frying, roasting and making them as meal.  The meal was processed into various processed foods, part of them were sold.